Preclinical evaluation of topically-administered PEGylated Fab' lung toxicity - Danielle Freches; Natacha Rocks; Harshad P. Patil; Fabienne Perin; Jacques Van Snick; Rita Vanbever; Didier Cataldo (Elsevier, 2019)
PEGylation is a promising approach to increase the residence time of antibody fragments in the lungs and sustain their therapeutic effects. However, concerns arise as to the potential pulmonary toxicity of antibody fragments conjugated to high molecular weight (HMW) polyethylene glycol (PEG), notably after repeated administrations, and the possibility of PEG accumulation in the lungs. The purpose of this proof-of-concept study is to give insights about the safety of lung administration of a Fab' anti-IL17A antibody fragment conjugated to two-armed 40 kDa PEG (PEG40). The presence of the PEG40 moiety inside alveolar macrophages remained stable for at least 24 h after intratracheal administration of PEG40-Fab' to mice. PEG40 was then progressively cleared from alveolar macrophages. Incubation of PEG40 alone with macrophages in vitro did not significantly harm macrophages and did not affect phagocytosis or the production of inflammatory markers. After acute or chronic administration of PEG40-Fab' to mice, no signs of significant pulmonary toxicity or inflammatory cell accumulation were observed. A vacuolization of alveolar macrophages not associated with any inflammation was noticed when PEG40, PEG40-Fab', or unPEGylated Fab' were administered. To conclude this preliminary proof of concept study, acute or repeated pulmonary administrations of PEGylated Fab' appear safe in rodents. Keywords: Pulmonary drug delivery, Monoclonal antibodies, PEGylation, Lung toxicity, Alveolar macrophages